Peran Struktur Organisasi dalam Distribusi Beban Kerja Guru dan Tenaga Pendidikan di SMP N 1 Kalibening: The Role of Organizational Structure in the Distribution of Workload of Teachers and Educational Personnel at SMP N 1 Kalibening - Amru Setyawinta; Ainas Sa’adah; Abdul Wahid (ITScience (Information Technology and Science), 2026)
The school's organizational structure plays a strategic role in determining the distribution of workload among teachers and educational staff. However, in practice, there is often a gap between the formal structure and the reality of task distribution in the field. This study aims to analyze the influence of organizational structure on the distribution of the workload for teachers and educational staff at SMPN 1 Kalibening and to identify the alignment between the structural design and actual work practices. The study used a qualitative case study design. Data were collected through in-depth interviews, participant observation, and documentation studies, and were then analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. The results show that the organizational structure has been formally designed based on school needs, individual competencies, and periodic evaluations. However, in its implementation, there is still flexibility in roles and additional tasks beyond formal job descriptions. This condition reflects the semi-formal and adaptive nature of the organization, which aligns with the concept of a loosely coupled system in educational organizations. Workload distribution is influenced not only by the administrative structure but also by leadership dynamics, internal coordination, and the school's contextual needs. These findings confirm that an organization's structure is effective not only by its formal design but also by its alignment with actual work practices. Therefore, it is necessary to strengthen data-based workload evaluation and formalize additional tasks to create a fairer, more proportional, and sustainable workload distribution.